PERSEPSI GURU BAHASA INDONESIA TERHADAP IMPLEMENTASI KURIKULUM DEEP LEARNING DI SEKOLAH DASAR ISLAM TERPADU AL MADINAH BENDAR - Putri Rizkia Fadhila; Heny Kusmawati; Ulfaatul Afidah; Sri Aji Pamungkas; Joko Prasetiyo; Muhammad Taufikurrohim; Syakira Deliilah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore teachers’ perceptions regarding the implementation of the Deep Learning curriculum at Al Madinah Elementary School, Bendar Juawana. Deep Learning emphasizes deep conceptual understanding as well as students’ critical and creative thinking skills. Using a qualitative approach, data were collected through in-depth interviews and questionnaires involving Indonesian language teachers from grades one to six. The findings of the study indicate that most teachers have a positive view of the curriculum, considering it a progressive step toward improving the quality of education. However, challenges remain in areas such as teacher training, availability of resources, and institutional support, which need to be addressed. The study recommends strengthening teacher training programs and promoting collaboration among teachers to optimize the curriculum's implementation. These findings are expected to provide insights for policymakers and educational institutions in developing a more effective and relevant curriculum framework.